A1 Noradrenergic Neurons Lesions Reduce Natriuresis and Hypertensive Responses to Hypernatremia in Rats - da Silva, Elaine Fernanda; Freiria-Oliveira, André Henrique; Custódio, Carlos Henrique Xavier; Ghedini, Paulo César; Bataus, Luiz Artur Mendes; Colombari, Eduardo [UNESP]; de Castro, Carlos Henrique; Colugnati, Diego Basile; Rosa, Daniel Alves; Cravo, Sergio L. D.; Pedrino, Gustavo Rodrigues (Public Library of Science (PLoS), 2013)
Noradrenergic neurons in the caudal ventrolateral medulla (CVLM; A1 group) contribute to cardiovascular regulation. The present study assessed whether specific lesions in the A1 group altered the cardiovascular responses that were evoked by hypertonic saline (HS) infusion in non-anesthetized rats. Male Wistar rats (280-340 g) received nanoinjections of antidopamine-β-hydroxylase-saporin (A1 lesion, 0.105 ng.nL-1) or free saporin (sham, 0.021 ng.nL-1) into their CVLMs. Two weeks later, the rats were anesthetized (2% halothane in O2) and their femoral artery and vein were catheterized and led to exit subcutaneously between the scapulae. On the following day, the animals were submitted to HS infusion (3 M NaCl, 1.8 ml • kg-1, b.wt., for longer than 1 min). In the sham-group (n = 8), HS induced a sustained pressor response (ΔMAP: 35±3.6 and 11±1.8 mmHg, for 10 and 90 min after HS infusion, respectively; P<0.05 vs. baseline). Ten min after HS infusion, the pressor responses of the anti-DβH-saporin-treated rats (n = 11)were significantly smaller(ΔMAP: 18±1.4 mmHg; P<0.05 vs. baseline and vs. sham group), and at 90 min, their blood pressures reached baseline values (2±1.6 mmHg). Compared to the sham group, the natriuresis that was induced by HS was reduced in the lesioned group 60 min after the challenge (196±5.5 mM vs. 262±7.6 mM, respectively; P<0.05). In addition, A1-lesioned rats excreted only 47% of their sodium 90 min after HS infusion, while sham animals excreted 80% of their sodium. Immunohistochemical analysis confirmed a substantial destruction of the A1 cell group in the CVLM of rats that had been nanoinjected withanti-DβH-saporin. These results suggest that medullary noradrenergic A1 neurons are involved in the excitatory neural pathway that regulates hypertensive and natriuretic responses to acute changes in the composition of body fluid. © 2013 da Silva et al.
Keywords: dopamine beta monooxygenase; saporin; sodium; animal cell; animal experiment; animal model; animal tissue; blood pressure; body fluid; bradycardia; cardiovascular response; chemoreceptor reflex; controlled study; hemoglobin blood level; hypernatremia; hypertension; immunohistochemistry; male; natriuresis; nonhuman; noradrenergic nerve; pressor response; pressoreceptor reflex; rat; sodium blood level; sodium urine level